School Processes and Internal Efficiency: What is the Relationship with the Academic Achievement in Mexican Vocational Schools? - Ramirez-Zambrano, Ademir Alfredo; Velasco-Arellanes, Francisco Justiniano; Vera-Noriega, José Ángel (Education Policy Analysis Archives, 2015)
The countries OECD members, including Mexico, have been considering important, for global economic development, the assessing of educational systems. In this regard, academic achievement has been considered an indicator of good education policies. In the present study we carry out an analysis of SIGEEMS databases to identify the relationship between School achievement and Processes Internal Efficiency in a sample of 585 vocational Schools. We carry out an analysis by Maximum-likelihood Paths, and we found that schools with cases of desertion have lower levels of academic achievement; greater numbers of students are positioned at insufficient reading and math skills. Conversely, if there are few students in desertion status, then there is a good and excellent domain in reading and math skills. These results together indicate that, to improve the Mexican Vocational School (High School Technology), SEP should know conditions of the students who tend to drop out or stay in groups with many students.